2013
DOI: 10.1002/jgrd.50337
|View full text |Cite
|
Sign up to set email alerts
|

Influence of summer monsoon diurnal cycle on moisture transport and precipitation over eastern China

Abstract: [1] Diurnal variability of the summer monsoon over China, a key element affecting regional climate, is examined using the latest reanalysis dataset and satellite rain estimates. Diurnal variation of low-level wind is found to be pronounced over South China during active monsoon days. Mean wind speed attains a maximum (minimum) in early morning (afternoon), with a diurnal range of 2-3 m/s, double that of inactive monsoon days. The largest amplitude typically appears at 850 hPa, consistent with radiosonde observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 65 publications
7
38
0
Order By: Relevance
“…Previous studies using satellite data showed that precipitation associated with MCCs lingered past midnight, and the size grew in nocturnal hours (e.g., Chen et al 2012;Ichikawa and Yasunari 2006). The evolution of different RREs corresponds to different cloud features.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…Previous studies using satellite data showed that precipitation associated with MCCs lingered past midnight, and the size grew in nocturnal hours (e.g., Chen et al 2012;Ichikawa and Yasunari 2006). The evolution of different RREs corresponds to different cloud features.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…One focus is the LLJ, recognized as a crucial factor for system organization, maintenance, and propagation (e.g., Trier et al 2006Trier et al , 2010Chen et al 2013;Sun and Zhang 2012) and controlled largely by synoptic conditions (e.g., Wang et al 2012), but few studies have addressed its roles in real cases, at least not in the context of rainproducing episodes. However, case studies are still few compared to climatological studies, especially in East Asia.…”
Section: B Motivation and Study Objectivesmentioning
confidence: 99%
“…Features such as the windward slope and the convergence region of a mountain produce more rainfall. Furthermore, a low-level jet plays an important part in the rainy season-for example, by causing the rainfall to increase during the late night and morning (Huang 1986;Xue 1999;Chen et al 2013). Although topographic features and the low-level jet clearly influence rainfall in the region, our focus here is on the local surface-air exchange and interactions.…”
Section: Introductionmentioning
confidence: 99%